VALORIZACIJA "KRUŽNOG" OBLIKA RADA ZA RAZVOJ DINAMIČKE SNAGE U NASTAVI FIZIČKOG VASPITANJA - Slobodan Stojiljković; Nataša Branković; Dejan Stojiljković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
For the realization of the research a sample of 90 examined of 11 years of age from Niš was used. The sample was divided into two sub samples, namely, an experimental group of 45 examinees and a control group of 45 examinees. With the experimental group, the "circular" form of work in the main part of the class for the physical strength development was applied. The control group had regular physical education classes. With both the examined groups, two measurements of dynamic strength (initial and final) were made in order to estimate the latent dimensions of explosive and repetitive strength. In order to assess explosive strength, the following variables were used, namely,1) standing long jump (MSDM), 2) standing triple jump (MTRS), and 3) ball throwing (MBLP). For the testing of repetitive strength the following tests were used, 1) torso lifting from the box (MDTK), 2) push-ups (MSKL) and 3) squats (MČUČ). The aim of the research was to determine the effects of the "circular" form of work upon the physical strength development in a three-month session of the physical education teaching. By the multivariant analysis of the variant it was determined that the examined of the experimental group increased, in the statistically significant way, the level of their dynamic strength in the final in comparison to the initial measurement.